Wastewater analysis: the mean of the monitoring of frequently prescribed pharmaceuticals in Slovakia - Mackuľak, Tomáš; Birošová, Lucia; Gál, Miroslav; Bodík, Igor; Grabic, Roman; Ryba, Jozef; Škubák, Jaroslav (Environmental monitoring and assessment, 2016)
The estimation of medication use is based on the statistical data from pharmacies and hospitals. Excessive use or misuse of some compounds, especially psychoactive medications, has not yet been monitored in Slovakia. Wastewater analysis provides useful data about the medication use and misuse in individual regions. This study is focused on the analysis of 23 substances in the wastewaters of Slovakia. The monitoring programme has included stimulants, opioid and morphine derivatives, benzodiazepines, antidepressants, drug precursors and their metabolites. Urinary markers of these compounds were analysed at WWTP influent in seven regions (Bratislava, Košice, Zvolen, Banská Bystrica, Trenčín, Prešov a Piešťany) using LC-MS/MS technique. The analysis was performed from March to October 2013. The pattern in use of these compounds was also monitored. Tramadol and venlafaxine were found to be the most concentrated compounds among of all studied psychoactive pharmaceuticals. The highest specific loads of tramadol were detected in Piešťany (409 mg/day/1000 inhabitants) and Zvolen (366 mg/day/1000 inhabitants). There is a considerable number of spa facilities (hotels) situated in these cities and this fact contributes to a higher occurrence of these psychoactive compounds in respective wastewaters.
Keywords: monitorování životního prostředí; Waste Water; Monitoring; odpadní voda; Cities; LC-MS/MS; Environmental Monitoring; Psychoactive pharmaceuticals; chemické látky znečišťující vodu; Waste Disposal, Fluid; odpad tekutý - odstraňování; Slovakia; Slovenská republika; Water Pollutants, Chemical; léčivé přípravky; Humans; Wastewater; Drugs; Tandem Mass Spectrometry; chromatografie kapalinová; velkoměsta; Pharmaceutical Preparations; tandemová hmotnostní spektrometrie; Chromatography, Liquid; lidé